PELATIHAN PEMAKAIAN DAN PERAWATAN ALAT PENJERNIH AIR SIAP MINUM UNTUK SANTRIWATI PONDOK PESANTREN - Sugianto, Erik; Dewantara, Belly Yan; Prasutiyon, Hadi; Sakti, Gedhe Angkoso Nur Sofa (Jurnal Abdi Insani, 2024)
Al-Karimiyyah Islamic Boarding School in Sumenep faces problems in water supply. The female students are forced to use brackish well water for drinking because the availability of potable water is limited, while using the services of a gallon water provider is very expensive. The need for drinking water must be met on an ongoing basis given the large number of female students and staff living there. This training activity aims to increase knowledge and understanding of the use of the reverse osmosis method water purifier. As well as improving the quality of water so that it is suitable for drinking.  The reverse osmosis system will treat and filter water to neutralise taste, odour, and harmful substances, so that it becomes ready-to-drink water. The training method was carried out through workshops and training on the use of tools with reverse osmosis systems that use solar power sources for female students in Beraji Village.  This activity was carried out for three days in the hall of Al-Karimiyyah Islamic boarding school, Braji village, Gapura sub-district, Sumenep district, East Java.   The boarding school residents learnt how to install and maintain a filtration device with reverse osmosis technology to provide ready-to-drink water. The device is placed outdoors for easy access by female students. Solar panel technology is used as the main power source so that this tool is independent in terms of electricity and can be placed in any location. This training activity is also an alternative to providing drinking water that is suitable for consumption, so that it can save time and money. In addition, santriwati also get education about the importance of consuming clean water to avoid disease. Santriwati now have sustainable access to clean drinking water. The application of reverse osmosis technology with solar power not only increases the availability of clean water, but also becomes a solution to electricity scarcity.